Inflammasome and pyroptosis in autoimmune liver diseases - Wang, Jixuan; Sun, Zhiwen; Xie, Jingri; Ji, Wanli; Cui, Yang; Ai, Zongxiong; Liang, Guoying (Frontiers in Immunology, 2023)
Autoimmune hepatitis, primary biliary cholangitis, primary sclerosing cholangitis, and IgG4-related sclerosing cholangitis are the four main forms of autoimmune liver diseases (AILDs), which are all defined by an aberrant immune system attack on the liver. Most previous studies have shown that apoptosis and necrosis are the two major modes of hepatocyte death in AILDs. Recent studies have reported that inflammasome-mediated pyroptosis is critical for the inflammatory response and severity of liver injury in AILDs. This review summarizes our present understanding of inflammasome activation and function, as well as the connections among inflammasomes, pyroptosis, and AILDs, highlighting the shared features across the four disease models and the gaps in our knowledge. In addition, we summarize the correlation among NLRP3 inflammasome activation in the liver-gut axis, liver injury and intestinal barrier disruption in PBC and PSC. We summarize the differences in microbial and metabolic characteristics between PSC and IgG4-SC, and highlight the uniqueness of IgG4-SC. We explore the different roles of NLRP3 in acute and chronic cholestatic liver injury, as well as the complex and controversial crosstalk between various types of cell death in AILDs. We also discuss the most up-to-date developments in inflammasome- and pyroptosis-targeted medicines for autoimmune liver disorders.